Case Report: Low Dose of Valsartan/Sacubitril Leads to Successful Reversal of Acute Heart Failure in Chemotherapy-Induced Cardiomyopathy - Lo, Shih-Hsing; Liu, Yi-Ching; Dai, Zen-Kong; Chen, I-Chen; Wu, Yen-Hsien; Hsu, Jong-Hau (Frontiers in Pediatrics, 2021)
Sacubitril/Valsartan is a new agent approved for the treatment of chronic heart failure in adults, with combination of angiotensin receptor inhibitor and neprilysin inhibitor. However, the benefit of sacubitril/valsartan in pediatric patients is unknown. We herein report its clinical benefit in a case of acute decompensated heart failure in chemotherapy-induced cardiomyopathy. This case suggest that in children with acute heart failure refractory to conventional medications, low dose of Sacubitril/Valsartan may be an effective therapy.